2004
DOI: 10.1177/0269881104042634
|View full text |Cite
|
Sign up to set email alerts
|

Oral Transmucosal Abuse of Transdermal Fentanyl

Abstract: Transdermal fentanyl is an opioid analgesic that is effective on chronic pain, and which appears to be advantageous due to several factors such as ease of administration, the relatively stable serum concentration and long dose intervals. Nevertheless, the danger of abuse and dependence exists among patients who are prescribed fentanyl patches. We present a case of transdermal fentanyl abuse, where the administration route of the drug was changed. Our patient, who had no history of substance abuse and who suffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…[29] In the same study, fentanyl was found to be more likely to be associated with alternative routes of abuse than other prescription opioid analgesics (i.e., abuse via routes other than that intended or via inhalation, injection or chewing); 70% of individuals abusing transdermal fentanyl and 69% of those abusing sublingual fentanyl reported other routes of abuse compared with 3-13% for other drugs. [29] Other routes of abuse that have been reported for transdermal fentanyl formulations include application of multiple patches, [38] placing the patch in the mouth, [39][40][41] chewing or sucking, [42][43][44] swallowing whole, [45,46] injection of extracted patch contents, [47][48][49] smoking [50,51] and rectal insertion. [52] Patches may also be boiled to make a "tea", which can be ingested or injected.…”
Section: Differences In Routes Of Abuse Between Formulationsmentioning
confidence: 99%
“…[29] In the same study, fentanyl was found to be more likely to be associated with alternative routes of abuse than other prescription opioid analgesics (i.e., abuse via routes other than that intended or via inhalation, injection or chewing); 70% of individuals abusing transdermal fentanyl and 69% of those abusing sublingual fentanyl reported other routes of abuse compared with 3-13% for other drugs. [29] Other routes of abuse that have been reported for transdermal fentanyl formulations include application of multiple patches, [38] placing the patch in the mouth, [39][40][41] chewing or sucking, [42][43][44] swallowing whole, [45,46] injection of extracted patch contents, [47][48][49] smoking [50,51] and rectal insertion. [52] Patches may also be boiled to make a "tea", which can be ingested or injected.…”
Section: Differences In Routes Of Abuse Between Formulationsmentioning
confidence: 99%
“…However, more experienced abusers may alter the method of administration to increase the rate of absorption in an attempt to experience a more intense euphoria. Published case reports describe FTP abuse via excessive transdermal application, use of heating pads to increase cutaneous absorption, application to the oral or rectal mucosa, mastication of patches, ingestion of intact patches, ingestion of the gel reservoir, intravenous injection of patch contents, volatilization and inhalation of the gel reservoir, and ingestion of FTP ''tea'' (22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation of the patches has also been reported,10 and a fatal overdose of transdermal fentanyl by the oral mucosal route was described by Kramer and Tawney 11. Liappas et al 12 report the case of a patient who abused fentanyl patches by leaving them in her oral cavity for increased analgesia for non-malignant pain. Liappas et al note that using fentanyl transmucosally results in different pharmacokinetics compared to the transdermal route.…”
Section: Discussionmentioning
confidence: 99%